Digitalization of bullion trading: A rapid systematic literature review based on strategic management 5.0 framework - Hari Imbrani; Indri Yani (EcoProfit: Sustainable and Environment Business, 2026)
Background: The digitalization of bullion trading has accelerated rapidly due to technological advancement and market demand for more efficient, transparent, and inclusive investment access. Despite growing implementation across platforms, the academic literature remains fragmented in explaining the dominant themes, key benefits, and strategic risks of bullion trading digital transformation. Methods: This study employed a rapid systematic literature review (RSLR) approach using PRISMA guidelines to identify, screen, and synthesize relevant scholarly publications on digital bullion trading. Articles were collected from major academic databases, filtered using predefined inclusion–exclusion criteria, and analyzed using thematic synthesis to map conceptual patterns and research trends. Findings: The review reveals four dominant themes: technology adoption and platform innovation, trading efficiency and market accessibility, regulatory and governance challenges, and risk management including cybersecurity and fraud. Digital bullion trading strengthens market inclusivity and transaction speed but also increases exposure to technological, compliance, and trust-related risks. Furthermore, regulatory readiness and institutional governance emerge as critical enablers for sustainable digital bullion ecosystems. Conclusion: Digitalization in bullion trading provides strategic advantages in operational efficiency, market expansion, and customer experience; however, long-term sustainability requires stronger governance frameworks, regulatory harmonization, and enhanced risk mitigation strategies. Future studies should integrate cross-country comparisons and empirical testing of digital trading performance models. Novelty/Originality of this article: This study provides an updated thematic mapping of digital bullion trading research using an RSLR-PRISMA approach, offering strategic insights that connect technological innovation, regulatory dynamics, and sustainability of bullion trading ecosystems.